FINANCIAL DISTRESS ANALYSIS WITH ZMIJEWSKI X-SCORE METHOD IN ISLAMIC BANKING COMPANIES (CASE STUDY OF THE INDONESIA STOCK EXCHANGE) - Husain; Purnamasari, Rini; Indrayani (Institut Agama Islam Negeri Parepare, 2025)
Financial distress or financial difficulty is a situation where the company's financial position has decreased so that the company is unable to meet its short-term debt and long-term debt obligations, so it is necessary to analyze the company's finances in order to see the condition of the company. this study aims to analyze the level of bank health using the zmijewski x-score method at Islamic banks listed on the Indonesia Stock Exchange for the period 2021-2023. This study uses a descriptive quantitative method whose data sources come from secondary data in the form of financial reports of Islamic banks listed on the Indonesia Stock Exchange for 2021- 2023 with a sampling technique using saturated sampling. The results of this study indicate that the health level of Islamic banks on the Indonesia Stock Exchange (IDX) which is analyzed using the zmijeski x-score method for the 2021-2023 period with the zmijewski model which has a cut off value of 0, with assessment criteria if the company's financial distress prediction score is less than 0 (X < 0), then the company is in a non-financial distress or healthy zone. Meanwhile, if the company's financial distress prediction score is more than 0 (X> 0), then the company is predicted to enter the financial distress zone or go bankrupt. In general, the level of bank health during the 3 periods was in a healthy condition (nonfinancial distress). Thus, a good level of bank health reflects a healthy Islamic bank so that it can be considered capable of dealing with significant negative influences from business conditions and other factors.